QUALITY OF WORK LIFE SEBAGAI SOLUSI PENINGKATAN KINERJA KARYAWAN DALAM PERSPEKTIF ISLAM - Raziki Waldan (Jurnal Al-Hikmah: Jurnal Dakwah, 2018)
Quality of Work Life is a very important aspect to be considered in improving the performance of an organization. This paper aims to describe and conclude the concept of Quality of Work Life from an Islamic perspective. This paper is a literature review, so this study uses the literature study method. Literature study is carried out by reviewing articles both in the form of scientific journals and papers as well as literature studies of books with sources that are considered accurate and reliable. Searching techniques of literature study are carried out both online as well as library book visits. The study results concluded that: 1). Quality of Work Life is a concept that talks about the welfare and happiness of employees' lives at work, 2). In the Islamic concept Quality of Work Life can be seen from the aspects of: a. Fulfillment of Life Needs Fairly, Transparent and Fair, b. Employee Satisfaction in a Conducive Environment, c. Giving Reward and Punishment, c. Good Humanitarian Relations in Organizations Between Fellow Employees also Between Employees and Organizational Management. (Quality of Work Life merupakan aspek yang sangat penting untuk diperhatikan dalam peningkatan kinerja sebuah organisasi, Tulisan ini bertujuan untuk menguraikan dan menyimpulkankan konsep Quality of Work Life dari perspektif Islam. Tulisan ini merupakan sebuah kajian literatur, maka kajian ini menggunakan metode studi kepustakaan. Studi kepustakaan dilakukan dengan mereview artikel baik dalam bentuk jurnal ilmiah dan makalah juga studi pustaka buku- buku dengan sumber-sumber yang dianggap akurat dan dapat dipercaya. Teknik penelusuran studi kepustakaan dilakukan baik secara online juga secara kunjungan buku perpustakaan. Hasil kajian menyimpulkan bahwa: 1). Quality of Work Life merupakan konsep yang berbicara tentang kesejahteraan dan kebahagiaan hidup karyawan dalam bekerja, 2). Dalam konsep Islam Quality of Work Life dapat dilihat dari aspek: a. Pemenuhan Kebutuhan Hidup Secara Wajar, Transparan dan Adil, b. Kepuasan Karyawan dalam Lingkungan yang Kondusif, c. Pemberian Reward dan Punishment, c. Hubungan Kemanusiaan yang Baik dalam Organisasi Antara Sesama Karyawan juga Antara Karyawan dan Manajemen Organisasi).